The Psychic Activities of the Main Characters in the Novel Tempat Paling Sunyi by Arafat Nur - Lili Yanti; Nelly Herniaty; Rahmatika Dewi; Heru Susanto; Gunta Wirawan; Kamaruddin Kamaruddin (International Journal of Multi Discipline Science, 2022)
This study aims to describe the psychic activity of the main character in Arafat Nur's novel Tempat Paling Sunyi which includes cognitive symptoms, affective symptoms, and conative symptoms. This research method was a descriptive method with a qualitative research form. This study used a literary psychology approach. The source of the data for this research was the novel Tempat Paling Sunyi by Arafat Nur (2015). The data in this study were in the form of quotations (words, phrases, and sentences). Data collection techniques used direct techniques, namely documentary techniques with data collection tools, namely the researchers themselves as key instruments and data recording cards. The data analysis technique used descriptive text analysis techniques. Checking the validity of the data was done by peer checking techniques through discussion and triangulation. Based on the analysis of Arafat Nur's novel of Tempat Paling Sunyi, it can be concluded that the cognitive symptoms in the novel of Tempat Paling Sunyi are attention, observation, response, fantasy, thought, memory, intuition; affective symptoms in the novel of Tempat Paling Sunyi are feelings, affect and stemming, moods; conative symptoms in the novel of Tempat Paling Sunyi are automatism, reflex, instinct, lust, desire, desire.